Equations Used to Calculate Vertical Bearing Capacity of Driven Piles with Shaft Broadenings - Atenov, Yerlan; Bekbasarov, Isabai (Periodica Polytechnica Civil Engineering, 2020)
In a pile foundation setting practice driven piles with an unconventional (variable) longitudinal shape of surface are widely used. Such piles are made with various slopes of the side faces, may have different types of broadenings, thickenings, etc. The effectiveness of such piles is due to their design features, allowing full use of the natural bearing capacity of the soil base without additional reinforcement. The obvious advantages of these piles make it relevant to study the features of their interaction with the soil stratum, especially the bearing capacity of piles. This study was aimed to investigate vertical bearing capacity of driven reinforced concrete piles with several broadening of the shaft. Numerical calculations and experimental studies of the bearing capacity of piles with broadening under the static loading have been carried out. Equations for calculating the bearing capacity of piles with broadenings are proposed and their verification is performed. The equations include a coefficient that takes into account the features of soil behavior underneath of the pile broadening during palification. Correlation dependence is presented which makes it possible to determine the values of that coefficient depending on the number of pile broadening and the liquidity index of soil. A correlation that makes allow calculations the bearing capacity of piles with broadening via the bearing capacity of a prismatic pile is proposed. The equations are recommended to be used at the stage of variant design of piles with broadening as part of the pile foundations of buildings and structures.